Plant Interaction Patterns Shape the Soil Microbial Community and Nutrient Cycling in Different Intercropping Scenarios of Aromatic Plant Species - Sun, Yue; Chen, Li; Zhang, Shiyi; Miao, Yantao; Zhang, Yan; Li, Zhenglin; Zhao, Jingya; Yu, Lu; Zhang, Jie; Qin, Xiaoxiao; Yao, Yuncong (Frontiers in Microbiology, 2022)
Intercropping systems improve the soil nutrient cycle through microbial community activity and then land productivity. However, the mechanism of aromatic plant mixture introduction to under-forest vegetation and how their intraspecific and interspecific interactions regulate the soil microbial community is unclear. We designed treatments with 0, 1 and 3 aromatic plant species intercropped in two scenarios of clean tillage (T model, T1, T2 and T4) and natural grass (G model, G1, G2 and G4) in apple orchards, and analysed them at the branch growing stage (BGS) and fruit development stage (FDS), respectively. G4 had the lowest soil PLFAs (Phospholipid fatty acids) but a high B/F ratio, while T4 had a low B/F ratio in the FDS. T4 promoted the Sob, Chao and Shannon indices of bacterial and fungal communities, while G4 decreased them in the FDS. G4 relative to T4 promoted beta diversity of fungal community more than that of bacterial community. T4 increased the relative abundance of many dominant microbes, such as Sphingobacteria and Nitrospirae, while G4 decreased the relative abundance of Caulobacterales, Woodsholea and Micrococcales in the BGS and FDS. The co-occurrence network revealed that most network indices and hubs were reduced by T4 to lower than those of T1 and reduced by G4 to values higher than those of G1. T4 promoted INV activity in BGS and SOC (soil organic content), AP (available P) and URE (soil urease) activity and lowered the C/P ratio in the FDS. G4 promoted SOC and the C/N and C/P ratios but decreased SWC (soil water content) and ACP (soil acid phosphatase) activity and lowered the C/P ratio in the FDS, with higher values in SMF (soil multifunctionality index) than in T4. These results suggested that mixed intercropping remarked regulate microbial community via the species diversity and decomposition, and chemical diversity and antimicrobial activity of litter mixtures in T and G model respectively. Based on the above results, our study presents a new method to improve the soil nutrient cycle, where intercropping patterns and development stages of fruit trees regulate microbial community complexity and stability, which may benefit fruit development and quality improvement.